Improved semipolar green InGaN/GaN quantum wells on asymmetrically grown (112̄2) GaN templates and their correlations. Issue 14 (23rd March 2018) - Wu, Zhengyuan; Shih, Tienmo; Li, Jinchai; Tian, Pengfei; Liu, Ran; Kang, Junyong; Fang, Zhilai
Abstract : Asymmetric island sidewall growth (AISG) is employed to reduce the threading defect density and to modify the surface/interface properties of semipolar GaN templates and InGaN/GaN quantum wells (QWs). Abstract : Asymmetric island sidewall growth (AISG) is employed to reduce the threading defect density and to modify the surface/interface properties of semipolar GaN templates and InGaN/GaN quantum wells (QWs). We have found that the microstructures and optical properties of the semipolar InGaN/GaN QWs are well correlated with the threading defect density and surface properties of semipolar growth templates. Without AISG, surface undulation, indium fluctuation, and a relatively high indium content within InGaN layers on conventional GaN templates are observed and correlated with high-density threading defects and the formation of specific microfacets with more N dangling bonds on the surface. With AISG, these semipolar InGaN/GaN QWs on modified GaN templates exhibit a uniform indium distribution in the absence of threading defects. The optical properties of InGaN/GaN QWs are significantly improved, and this improvement is attributed to the surface modification of GaN templates, the reduction in threading defect density, and the higher uniformity of indium distribution within InGaN layers.